Gene‐based mapping of trehalose biosynthetic pathway genes reveals association with source‐ and sink‐related yield traits in a spring wheat panel. (7th May 2021) - Lyra, Danilo H.; Griffiths, Cara A.; Watson, Amy; Joynson, Ryan; Molero, Gemma; Igna, Alina‐Andrada; Hassani‐Pak, Keywan; Reynolds, Matthew P.; Hall, Anthony; Paul, Matthew J.
Abstract: Trehalose 6‐phosphate (T6P) signalling regulates carbon use and allocation and is a target to improve crop yields. However, the specific contributions of trehalose phosphate synthase (TPS) and trehalose phosphate phosphatase (TPP) genes to source‐ and sink‐related traits remain largely unknown. We used enrichment capture sequencing on TPS and TPP genes to estimate and partition the genetic variation of yield‐related traits in a spring wheat ( Triticum aestivum ) breeding panel specifically built to capture the diversity across the 75, 000 CIMMYT wheat cultivar collection. Twelve phenotypes were correlated to variation in TPS and TPP genes including plant height and biomass (source), spikelets per spike, spike growth and grain filling traits (sink) which showed indications of both positive and negative gene selection. Individual genes explained proportions of heritability for biomass and grain‐related traits. Three TPS1 homologues were particularly significant for trait variation. Epistatic interactions were found within and between the TPS and TPP gene families for both plant height and grain‐related traits. Gene‐based prediction improved predictive ability for grain weight when gene effects were combined with the whole‐genome markers. Our study has generated a wealth of information on natural variation of TPS and TPP genes related to yield potential which confirms the role for T6P in resource allocation and in affecting traits such as grain number and size confirming other studies which now opens up the possibility of harnessing natural genetic variation more widely to better understand the contribution of native genes to yield traits for incorporation into breeding programmes. Abstract : The T6P signalling pathway is a central regulatory system of resource allocation and source‐sink interactions and is emerging as an important target in crops such as maize, rice, wheat and sorghum (Paul et al., 2018; Paul et al., 2020). Here, for the first time, we analysed comprehensive exome SNP information for TPS and TPP genes and dissected the genetic architecture of yield‐related traits in a spring wheat panel specially designed to represent the genetic diversity of 75, 000 CIMMYT lines (Molero et al., 2019). The data showed significant relationships of TPS and TPP genes with agronomic traits with evidence of historical selection and identified opportunities for future selection of TPS and TPP genes and strategic crossing for yield improvement.